Adventure Snake: A Game to Improve Symbolic Thinking Skills in Early Childhood - Nurjannah, Eka; Rismala, Nia; Melati, Sherin Azzahra Ismi; Julea, Thalitha Ariandinie; Utami, Winda Sherly; Amanda, Rizki Surya (Universitas Pendidikan Indonesia Kampus Serang, 2024)
The utilization of media is crucial for enhancing children's symbolic thinking. Authentic and stimulating media, such as adventure, enhances cognitive development in children. This study aims to investigate the influence of playing the Adventure Snake game on the advancement of symbolic thinking in early childhood. Qualitative research methods were employed through participatory observation of children aged 5 to 6 years engaged in the Adventure Snake game over a specified duration. Findings indicate that engagement with the Adventure Snake game enhanced children's capacity for creative symbol use, augmented their comprehension of spatial concepts, and fortified their cognitive abilities. This research underscores the significance of play in facilitating the development of symbolic thinking during early childhood. They must employ problem-solving and critical thinking abilities to determine the actions they will undertake. Additionally, the Adventure Snake game enhances children's concentration and memory since they must recall the number of steps taken and monitor alterations on the game board. Consequently, engaging in Adventure Snake can offer diverse cognitive stimulation and promote brain development in young children.